ANALISIS KEWENANGAN DAN KOMPETENSI APOTEKER DALAM STANDAR PELAYANAN KEFARMASIANDI PUSKESMAS - Toha Achmad Saputra, (2021)
ABSTRACT The standard of service of pharmacy of the Community Health Center in Indonesia shall be carried out by the Pharmacist and assisted by the Assistant of Pharmacist. Community Health Center shall be hereinafter referred to as the Puskesmas. The arrangement of regulation against the authority and responsibility, both, shall cause the legal uncertainty. This writing shall have purpose to analyze the authority and competency of the Pharmacist in the standard of service of pharmacy in the Puskesmas, pursuant to the Regulation of Minister of Health of the Republic of Indonesia Number 26 Year 2020 (hereinafter shall be referred to as PMK No. 26 Year 2020). This writing shall constitute the normative legal research, which use the secondary data. From the analysis result, it is found that the Pharmacist shall be authorize in the standard of service of pharmacy at the Puskesmas due to the expertise which attached to itself and the authority which provided by the law. Meanwhile PMK No. 26 Year 2020, there is no conformity between other laws, in relation to the arrangement of authority of pharmacy personnel between the Pharmacist and the Assistant of Pharmacist in te standard of service of pharmacy at the Puskesmas. The finding of this research shall be extremely beneficial to give the input to the government of the Republic of Indonesia to carry out reassessment against PMK No. 26 Year 2020 and immediately fulfill the need of the Pharmacist at the Puskesmas, in order to increase the quality of service, guarantee the legal certainty and protect the patient.